Computer aided evaluation of selected examination tasks in mathematics using generalized hough transform - Stoliński, Sebastian; Bieniecki, Wojciech (Wydawnictwo Politechniki Łódzkiej, 2014)
In this chapter an image processing algorithm for automatic evaluation of scanned examination sheets is described. The discussed image contains selected geometric figures drawn by hand on a printed coordinate system. This type of task is characteristic of final high school exams of natural sciences. Our challenge was to develop an evaluation algorithm, which works with a precision comparable to the teacher. If the image contains the correct solution, the algorithm should husk it from a set of random lines, deletions, amendments, drafts, bearing in mind, that lines were drawn by hand. In addition, the algorithm should calculate scores for partially correct solutions. An essential part of our proposal is based on Hough transform (for recognizing lines) and generalized Hough transform (for recognizing non linear shapes). The proposed solution is flexible and can be extended to other types of tasks such as drawing geometrical figures.[...]
Keywords: wspomagana komputerowo ocena egzaminów; algorytm oceny; transformacja Hougha; uogólniona transformacja Hougha; computer aided evaluation of exams; evaluation algorithm; Hough transform; generalized Hough transform